A novel Golgi-Cox staining method for detecting and characterizing roles of the hepatic stellate cells in liver injury. Issue 4 (December 2017) - Gómez Villalobos, Ma. de Jesús; Vidrio, Susana; Giles López, Ruth; Flores Gómez, Gabriel; Chagoya de Sánchez, Victoria
Abstract: The aim of this study was to investigate the utility of the Golgi-Cox method to characterize the distribution and morphological changes of the hepatic stellate cells (HSCs) in CCl4 liver damaged rats. Six-week-old male Wistar rats were injected with CCl4 for ten weeks. The livers were processed with the Golgi-Cox method, reticuline, and Massońs Trichrome stains, and analyzed under light microscopy. Histological evaluation of livers was made through the METAVIR score. In normal livers, the HSCs show stellate form with abundant thin cytoplasmic processes, distributed into hepatic lobule, mainly in zone 1. In addition, an intricate and broad network of fibers with radial distribution from the central vein to the periphery of the hepatic lobule was observed. In CCl4 damaged livers, with METAVIR score I and II, HSCs showed a moderate increase in the soma size, in the cytoplasmic processes and in density, distributed in zone 2 and 3; changes associated with a decrease in network fibers. In livers with METAVIR score III and IV, the morphology changes of the HSCs consisted of a significant increase in the soma size, cut and fraying appearance of the emerging cytoplasmic processes, and a decrease in HSCs density, distributed mainly in zone 3, with a significant depletion of network fibers. Results show that Golgi-Cox stain is able to impregnate the HSCs and could be an additional tool to study the morphological changes of the HSCs in the different experimental pathological conditions of the liver.